Negotiating learning: are shortcuts good or bad for our students? - Mohd Hashim, Intan Hashimah; Endut, Noraida; Azwan, Azman; Abdul Rahman, Shukran; , (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
Today’s increasingly globalised world places specific demands on young people pursuing tertiary education. There is a growing contention that students are increasingly “engaging in shortcut behaviour” due to the competitive nature of studies at Malaysian universities. Although the phrase has not been widely established in related academic areas as describing particular learning behaviour, “engaging in shortcut behaviour” may be operationally defined as a situation whereby, in order to achieve a particular learning result, a student undertakes courses of actions that are perceived to require lesser time and effort than are conventionally prescribed